2016
DOI: 10.1007/s12020-016-0878-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of several circulating microRNAs from a genome-wide circulating microRNA expression profile as potential biomarkers for impaired glucose metabolism in polycystic ovarian syndrome

Abstract: This study aimed to detect serum microRNAs (miRNAs) differentially expressed between polycystic ovary syndrome (PCOS) patients with impaired glucose metabolism (IGM), PCOS patients with normal glucose tolerance (NGT), and healthy controls. A TaqMan miRNA array explored serum miRNA profiles as a pilot study, then selected miRNAs were analyzed in a validation cohort consisting of 65 PCOS women with IGM, 65 PCOS women with NGT, and 45 healthy women The relative expression of miR-122, miR-193b, and miR-194 was up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…51 Scholars also found that miR-199b-5p was downregulated in PCOS and predicted the involvement of the PI3K-Akt signaling pathway in disease pathophysiology. 56 Moreover, in the endometrial cells of patients with PCOS-IR, the change in the PI3K-Akt signaling pathway was found to affect IR. Rivero et al 57 used telomerase-immortalized human endometrial stromal cells (T-HESCs) from PCOS with IR and observed that when T-HESCs were stimulated with insulin and testosterone, the protein levels of Munc18c and phospho-PKCz decreased.…”
Section: The Pi3k-akt Signaling Pathway and Irmentioning
confidence: 96%
“…51 Scholars also found that miR-199b-5p was downregulated in PCOS and predicted the involvement of the PI3K-Akt signaling pathway in disease pathophysiology. 56 Moreover, in the endometrial cells of patients with PCOS-IR, the change in the PI3K-Akt signaling pathway was found to affect IR. Rivero et al 57 used telomerase-immortalized human endometrial stromal cells (T-HESCs) from PCOS with IR and observed that when T-HESCs were stimulated with insulin and testosterone, the protein levels of Munc18c and phospho-PKCz decreased.…”
Section: The Pi3k-akt Signaling Pathway and Irmentioning
confidence: 96%
“…A genome-wide circulating miRNA expression profile identified a number of miRNAs dysregulated in women with PCOS. These miRNA species are involved in glycometabolism and ovarian follicle development pathways [111, 112]. Interestingly, miRNA-592 has been shown to be downregulated and to be inversely related to LHCGR levels in PCOS patients [113].…”
Section: A Pathophysiologymentioning
confidence: 99%
“…MicroRNAs (miRNAs, miRs) are evolutionarily conserved small noncoding RNA molecules that function as negative post-transcriptional gene regulators [ 6 ]. Because of the ability of a single miRNA molecule to target hundreds of messenger RNAs (mRNAs), abnormal miRNA expression is associated with the initiation of many diseases [ 7 ]. Recent studies have suggested that miRNAs may be involved in the development of GA [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%